Biosynthetic Activity Differs Between Islet Cell Types and in Beta Cells Is Modulated by Glucose and Not by Secretion - Cottet-Dumoulin, David (Endocrinology, 2020)
A correct biosynthetic activity is thought to be essential for the long-term function and survival of islet cells in culture and possibly also after islet transplantation. Compared to the secretory activity, biosynthetic activity has been poorly studied in pancreatic islet cells. Here we aimed to assess biosynthetic activity at the single cell level to investigate if protein synthesis is dependent on secretagogues and increased as a consequence of hormonal secretion. Biosynthetic activity in rat islet cells was studied at the single cell level using O-propargyl-puromycin (OPP) that incorporates into newly translated proteins and chemically ligates to a fluorescent dye by “click” reaction. Heterogeneous biosynthetic activity was observed between the four islet cell types, with delta cells showing the higher relative protein biosynthesis. Beta cells protein biosynthesis was increased in response to glucose while 3-isobutyl-1-methylxanthine and phorbol-12-myristate-13-acetate, 2 drugs known to stimulate insulin secretion, had no similar effect on protein biosynthesis. However, after several hours of secretion, protein biosynthesis remained high even when cells were challenged to basal conditions. These results suggest that mechanisms regulating secretion and biosynthesis in islet cells are different, with glucose directly triggering beta cells protein biosynthesis, independently of insulin secretion. Furthermore, this OPP labeling approach is a promising method to identify newly synthesized proteins under various physiological and pathological conditions.